Sosialisasi dan Pelatihan Quizizz sebagai Media Asesmen Pembelajaran Digital untuk Mahasiswa jurusan Matematika UISU - Siregar, Alwi Gery Agustan; Wahyuni, Ratna; Nasution, Haryati Ahda (-, 2025)
Digital transformation in education demands the use of interactive and adaptive assessment media, particularly in mathematics learning at the higher education level. This community service activity aims to enhance the competencies of students in the Mathematics Department of Universitas Islam Sumatera Utara (UISU) in utilizing Quizizz as a digital learning assessment tool. The methods employed include socialization, interactive training, discussions, and hands-on practice in creating and using Quizizz-based quizzes. The results indicate a high level of participant engagement during the training, with 100% of students actively involved in quiz creation practices, 81% participating in discussions, and 75% asking questions. This level of engagement had a positive impact on the effectiveness of Quizizz usage, as evidenced by increases in problem-solving speed by 21.4%, answer accuracy by 32.3%, student engagement scores by 46.6%, and conceptual understanding by 41.8% after the training. These findings demonstrate that a practice-based and participatory training approach is effective in improving the quality of digital assessment and students’ conceptual understanding. Therefore, Quizizz is recommended as an innovative digital assessment medium to support mathematics learning in higher education.